Upaya PSDKU MIK Ngawi Dalam Pendirian Pusat Layanan Kesehatan Kampus 5 Polije Sebagai Rintisan Teaching Factory (Tefa) - Ida Nurmawati; Kurniawan Erman Wicaksono; Budi Fajar Supriyanto; Salihati Hanifa; Ikha Nurjihan (Indonesian Journal Publisher, 2025)
PSDKU MIK Ngawi Regency was established since the enactment of Decree of the Minister of Education, Culture, Research and Technology of the Republic of Indonesia No. 161/D/OT/2023 dated 10 July 2023. Industry-based vocational education. Competency-based vocational education must be equipped with a teaching factory. Efforts are being made to support the achievement of PSDKU competency. MIK Ngawi plans to establish a teaching factory in the form of a health service facility/health clinic which is expected to become a practicum facility for MIK students. Community service activities will be carried out in 4 stages, namely identification of needs, preparation stage, implementation of activities, monitoring and evaluation stages. Problem solutions offered to partners include socializing the requirements for establishing a clinic, preparing a management structure for clinical services, fulfilling basic clinical health service facilities, and preparing SOPs for using equipment. Socialization of the requirements for establishing a clinic was carried out through FGD with the Head of Health Services, Ngawi Health Office. The results of the FGD include legal health services for an agency, at least in the form of a clinic, provided that the person in charge is a doctor who has a practice license and is supported by other health workers (nurses and midwives). The availability of health human resources at PSDKU MIK Ngawi includes nursing, midwifery and public health personnel, so there is a need for doctors to meet the requirements for establishing a clinic. After the clinic's organizational structure is formed, the next step is to register with DPMPTSP (Department of Investment and One-Stop Integrated Services) via online single submission (OSS). Suggestions for the need for medical personnel (doctors) to fulfill the requirements for establishing a clinic and fulfilling the clinic requirements documents refer to Minister of Health Regulation No. 14 of 2021 concerning Standards for Business Activities and Products in the Implementation of Risk-Based Business Licensing in the Health Sector.